Locust bean gum improved the gelling properties of fish gelatin in acidic environments and its application in acid gel gummies - Fen-Fen Wu; Zong-Cai Tu; Jie Cheng; Hui Wang; Zi-Zi Hu; Xiao-Mei Sha (npj Science of Food)
Abstract To address the “gel weakening” of fish gelatin (FG) under acidic conditions,this study investigates the enhancement of gel performance in FG through the incorporation of locust bean gum (LBG) and explores its feasibility for application in acidic gel systems. Results show that the gel properties of FG were significantly improved through LBG modification. At pH 3−7, gel strength and melting temperature of LBG-modified FG (FG-LBG) surpassed those of unmodified FG (524.68 ± 1.54 g, 28.86 ± 0.03 °C). Specifically, at pH 3, after LBG modification, the gel strength and melting temperature of FG increased by 62.65% and 29.44%, respectively. LBG alters the conformation of FG via electrostatic and hydrogen bonding interactions, forming a denser polymer network. The acidic gel gummies prepared from the FG modified with LBG exhibit superior gel properties and texture characteristics. This study provides a basis for the modification of FG under acidic conditions.